Fabrication of all-dimensional superhydrophobic mortar with enhanced waterproof ability and freeze-thaw resistance. (30th March 2020) - Wang, Wei; Wang, Shanlin; Yao, Daozhou; Wang, Xikui; Yu, Xinquan; Zhang, Youfa
Highlights: A novel form of all-dimensional superhydrophobic mortar was fabricated. The mortar block showed remarkable all-dimensional superhydrophobicity. The water absorption and permeability (for 120 h) were reduced by 13.5% and 10.7%. The obtained mortar displayed substantial freeze-thaw resistance. Abstract: Multi-scale hydrophilic materials make cement-based composites susceptible to water and corrosive media, which may seriously reduce cement-based composites' durability. Superhydrophobic materials, given their excellent water-repellent properties, can effectively alleviate these problems. However, superhydrophobicity failure occurs on surfaces after enduring various stresses in practical application. To further explore this, we fabricated an all-dimensional superhydrophobic mortar block which could maintain internal superhydrophobicity after breaking into pieces or scraping off the surface layer. The comprehensive performance metrics, including all-dimensional superhydrophobicity, anti-corrosion, self-cleaning, waterproofing ability, and freeze-thaw resistance, were investigated. The results showed that the mortar block's superhydrophobicity had not been lost after being impacted by water or weight, man-made destruction by file or sandpaper, immersion in various corrosive liquids, or pollution by sludge water or dirt. Furthermore, compared to the ordinary mortar, the water absorption and water permeability (for 120 h) and mass loss after 220 freeze-thaw cycles of the obtained superhydrophobic mortar were reduced by 13.5%, 10.7%, and 98.6%, respectively, illustrating substantial waterproofing ability and freeze-thaw resistance. These key properties may provide unique advantages for a wide range of applications in construction, bridge, decoration, transport, and transmit electricity.